Sociodemographic determinants of life satisfaction among grandparent caregivers - Xu, Yi; Zhang, Ling; Mao, Shuyuan; Zhang, Si; Peng, Shuzhen; Zhang, Qi; Wu, Wenwen; Tan, Xiaodong (Frontiers in Public Health, 2023)
Introduction It has become a common contemporary phenomenon for grandparents to provide care for young children in their family in both urban and rural areas. This study attempted to investigate psychological wellbeing and quality of life among grandparents involved in childcare in China, and to explore the relationships between sociodemographic characteristics, quality of life, and life satisfaction in this group. Methods Using stratified random cluster sampling, we conducted a survey of grandparent caregivers in Wuhan in November and December of 2020 (N = 1,640). Descriptive statistics to univariate analysis, multiple linear regression, and structural equation modeling were carried out. Results Across all respondents, mean scores on life satisfaction, sleep quality, and quality of life were 14.05 ± 3.50, 5.02 ± 3.37, and 74.51 ± 16.88, respectively. Marital status, income, chronic diseases, family relationships, and physical exercise were found to be associated with life satisfaction. The results of structural equation modeling indicated that quality of life, sleep quality, and sociodemographic characteristics may exert direct and indirect effects on life satisfaction. Mediating effects accounted for 30.0% of the total effects. Conclusion Overall, grandparent caregivers have poor life satisfaction, quality of life, and sleep quality. A higher household income, better relationships with family members, healthy lifestyle habits, and high-quality sleep may effectively help to improve life satisfaction among grandparent caregivers.